2015
DOI: 10.1038/srep12265
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PblB mediating galactose-specific adhesion in a successful Streptococcus pneumoniae clone

Abstract: The pneumococcal genome is variable and there are minimal data on the influence of the accessory genome on phenotype. Pneumococcal serotype 14 sequence type (ST) 46 had been the most prevalent clone causing pneumonia in children in Taiwan. A microarray was constructed using the genomic DNA of a clinical strain (NTUH-P15) of serotype 14 ST46. Using DNA hybridization, genomic variations in NTUH-P15 were compared to those of 3 control strains. Microarray analysis identified 7 genomic regions that had significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…The reduced ability of the 4496⌬⌽ mutant to adhere to live A549 cells and its reduced capacity to form a biofilm on fixed A549 monolayers are consistent with the reduced capacity of the mutant to establish infection within the lungs which was observed following intranasal challenge in mice. The impact of the ⌬⌽ mutation on adherence to Detroit 562 nasopharyngeal cells was less pronounced, which is consistent with the lesser, but still statistically significant, effect on colonization of the murine nasopharynx at 24 h. These findings are also consistent with the recently published report that phageencoded PblB plays a role in adherence to the lung epithelium in serotype 14 pneumococci (14). The fact that a difference was observed in the present study only at early time points, whereas the mutant serotype 14 strain was reduced in numbers in the lung over longer time periods, may be a function of the distinct virulence profiles.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The reduced ability of the 4496⌬⌽ mutant to adhere to live A549 cells and its reduced capacity to form a biofilm on fixed A549 monolayers are consistent with the reduced capacity of the mutant to establish infection within the lungs which was observed following intranasal challenge in mice. The impact of the ⌬⌽ mutation on adherence to Detroit 562 nasopharyngeal cells was less pronounced, which is consistent with the lesser, but still statistically significant, effect on colonization of the murine nasopharynx at 24 h. These findings are also consistent with the recently published report that phageencoded PblB plays a role in adherence to the lung epithelium in serotype 14 pneumococci (14). The fact that a difference was observed in the present study only at early time points, whereas the mutant serotype 14 strain was reduced in numbers in the lung over longer time periods, may be a function of the distinct virulence profiles.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, in our study significantly fewer platelets were found in the circulation of mice challenged with the wild type than in those challenged with the phage-deficient strain. While differences in platelet aggregation were not observed in blood smears, the PblB-encoding phage clearly has some impact on the number of circulating platelets, perhaps through its recently reported ability to mediate attachment to platelets (14). However, while the AR1 phage appears to have some impact on the early stages of lung infection by the serotype 1 strain, the mutant and the wild type progress to fulminant infection at similar rates.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study, we performed a genome-wide association study (GWAS) on 349 pneumococcal draft genomes of blood isolates from patients who were admitted with IPD to two Dutch hospitals. We identified a significant association between 30-day mortality and the presence of pblB , encoding a platelet binding protein that was also reported to function in adhesion (8). In a subsequent functional study, we investigated the induction of phage-derived pblB expression by fluoroquinolones in S. pneumoniae .…”
Section: Introductionmentioning
confidence: 99%